2013
DOI: 10.1186/2049-6958-8-35
|View full text |Cite
|
Sign up to set email alerts
|

R ole of interleukin 4 and its receptor in clinical presentation of chronic extrinsic allergic alveolitis: a pilot study

Abstract: Background: Th-2 cytokine milieu including interleukin 4 (IL-4) was detected in fibrotic lung diseases. Chronic extrinsic allergic alveolitis (EAA) may be also accompanied by marked fibrogenesis. The aim of this study was to determine if IL-4 and its receptor (IL-4R-alpha) play any role in the clinical presentation and pathogenesis of chronic EAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“… 13 In broad agreement with previous studies, we also noted an air-cultured hMSC secretome contained FGFb, GM-CSF, IFNr, IL1a, IL4, IL8, IL10, IL12, MCP1, TGFb, TNFa, and VEGF which may form the basis of a minimal air-cultured hMSC secretome. 6 , 46 49 Similarly, IL2, IL6, IL13, MIP1a, and RANTES lay below a detectable threshold in our experimentation.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“… 13 In broad agreement with previous studies, we also noted an air-cultured hMSC secretome contained FGFb, GM-CSF, IFNr, IL1a, IL4, IL8, IL10, IL12, MCP1, TGFb, TNFa, and VEGF which may form the basis of a minimal air-cultured hMSC secretome. 6 , 46 49 Similarly, IL2, IL6, IL13, MIP1a, and RANTES lay below a detectable threshold in our experimentation.…”
Section: Discussioncontrasting
confidence: 48%
“…A number of previous studies have analyzed the serum-free in vitro secretome of hMSCs. Biomolecules identified in the secretome of air-cultured hMSCs have included anti-inflammatory (IL4, IL10, IL13, and TGFb), 6 , 46 pro-inflammatory (IL2, IL12, IFNr, TNFa, and IL1a), 6 , 47 chemokines (Rantes, MCP1, IL8, and MIP1b), 6 , 48 hemopoietic (G-CSF, and GM-CSF), 6 and pleiotropic factors (IL6). 6 , 15 Substantial overlap and significant discrepancy is a key feature of hMSC secretome defining studies.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous [ 18 , 43 ] and present studies, we suggested that TNF-α levels are indicative of lung tissue inflammation, especially in the early phases of HP, rather than fibroproliferation. On the other hand, chronic stages of HP are characterized by more pronounced fibroproliferation rather than inflammation or granuloma formation, which is represented by an overexpression of IL-4Rα, as we previously described [ 44 ]. That is probably the reason why IL- 4Rα levels did not differ among the subgroups of IIP in our current study.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, culture supernatants obtained from the BAL of chronic HP patients presented higher IL-4 and lower IFN-γ(9). Studying the IL-4/IL-4R axis may also be useful to discriminate HP from sarcoidosis, as IL-4R BAL levels appear to differ, but this requires further validation [ 81 , 82 ]. Indeed, several studies comparing cytokine levels in the BAL of HP patients with controls and/or other ILDs have been published.…”
Section: Biomarkers In Fibrotic Hpmentioning
confidence: 99%